Пластинчастовусі фітофаги молодих насаджень сосни звичайної в лісових розсадниках, особливості біології та контроль чисельності в Центральному Лісостепу України - Коренчук, Євген Володимирович (НУБіП України, 2020)
Дисертація на здобуття наукового ступеня кандидата сільсько господарських наук зі спеціальності 16.00.10 «Ентомологія». Національний університет біоресурсів і природокористування України. Київ, 2020. У дисертації обґрунтовано та представлено оригінальну, екологічно спрямовану систему регулювання чисельності комплексу ґрунтових фітофагів: західного та східного травневих, мармурового, червневого та волохатого хрущів у розсадниках сосни звичайної, до основи якої покладено концепцію багаторічної програми насичення екосистеми ентомопатогенами (застосування препаратів Боверин, 5 % титр 900 млн/мл, Метаризин, 5 % с. п. титр 900 млн/мл, композиції Метаризин, 5 % с. п. + Steinernema feltiae 1,0–1,2 млн) до досягнення популяціями шкідників порогу зникнення. Причому застосування хімічних інсектицидів (Актара, 25 WG, в. г., Антихрущ Люкс, к. с.) передбачається лише на початковому етапі реалізації програми – навесні першого року і лише в період масового льоту та яйцекладки. Застосування засобів регулювання чисельності хрущів здійснюється з урахуванням порогів шкідливості, моделі яких враховують енергетичну потребу у живленні цих видів, біомасу кореневої системи рослин та ефективність технології захисту у попередній період. Для весняного, літнього та осіннього періодів порогові моделі різняться. Для лісових екосистем є доцільним збільшення у системі захисту біологічної частки до рівня 60–80 %, порівняно до відомого співвідношення хімічного і біологічного методів (60:40), оскільки останнє було встановлене для агроценозів із урахуванням прийнятного рівня збереження урожаю. Оцінка загрози розсадникам від ґрунтових фітофагів здійснюється для значних площ за оригінальним протоколом класифікаційної «штрафної системи» на основі бальної оцінки факторів ризику, а для локальних територій за допомогою статистичного методу на основі просторових розподілів критерію Сведберга відсотку загибелі рослин та «тиску» личинок на рослини(зменшення приросту). За результатами оцінки приймається управлінське рішення щодо застосування засобів регуляції чисельності.
The dissertation on competition of a scientific degree of the candidate of agricultural sciences on a specialty 16.00.10 «Entomology». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2020. The dissertation establishes biological and ecological features of the beetle complex. It is established that according to the indicators of female pupae mass, functional activity of gonads and fertility of females of pedunculate oak leaves is a substrate that optimizes the vital functions of females. In comparison with other deciduous species, the real fertility of females fed on oak leaves exceeds 1.5–2.5 times. The greatest threat to planting is larvae that have reborn from eggs laid during the period of mass egg-laying. Thus, these materials are the basis for the temporal localization of the use of various methods that lead to egg death. The distribution of larvae in the soil shows that in May (in April the larvae are quite deep – 90 % at a depth of 50–75 cm) the most technological for the introduction of biological products is a depth of 10–30 cm – in this layer is concentrated up to 75 % of larvae; in June-July the depth can be reduced to 20 cm –almost 100 % of phytophages are in the surface horizons; in early August, in dry weather, the larvae migrate to wetter soil layers, so it is advisable to make drugs a little deeper by 20–40 cm – their concentration here is up to 88 %, but in late August and throughout September, the larvae with sufficient soil moisture again in surface layers up to 30 cm – 60–88 % of the total, in late September and October-November the main number of larvae – up to 85 %, concentrates on the wintering depth of 50–75 cm, the introduction of the drug to this depth is technologically unjustified. The spatial structure of the concentration of beetle pupae in the soil layers was established. The unevenness of their distribution has patterns of ecological and physiological nature. Of the total, only 11.8 % of pupae were concentrated at a depth of up to 7 cm. The rate of their death for the period of spring reactivation was 65.2 %. The share of viable populations was only 34.8 %. In the following layers 8–15 cm, 16–24 and 25–35 cm 80.6 % of pupae were concentrated. Their death rate is 14.3–15.4 %, including from predators 2.1–6.7 %. Synoptic anomalies caused the death of 0.8–2.8 % of pupae. The viable share of the population is 84.6–85.7 %, which is a real threat to plantings. The paper presents an original, ecologically oriented system of regulating the number of soil phytophagous complexes: western and eastern May, marble, June and hairy beetles in nurseries of Scots pine, which is based on the concept of a long-term program of ecosystem saturation with entomopathogens, 5 % of drugs / ml, Metarizin, 5 % SP titer 900 million/ml, compositions Metarizin, 5 % SP + Steinernema feltiae 1.0–1.2 million) until pest populations reach the threshold of extinction. Moreover, the use of chemical insecticides (Aktara, 25 WG, v. g., Antichrush Lux, h. p.) is provided only at the initial stage of the program –in the spring of the first year and only during the period of mass flight and egg-laying. The initial efficacy of Boverin and Metarizin was 90 % – Boverin – 92 and Metarizin – 95 %, slightly inferior to Aktari – 97 %, but over the next month, with a general downward trend, the residual efficacy of Boverin (32 %) and Metarizin (45 %) significantly outweighed the effectiveness of the chemical insecticide (12 %). There is a significant tendency to reduce the effectiveness of Metarizin and Boverin: during the first 30 days the effectiveness of Metarizin decreases more rapidly, then stabilizes and decreases more slowly, in Boverin, on the contrary, in the first stage the effectiveness decreases more slowly, and finally decreases sharply. Their effectiveness coincides at different levels on approximately the 7th (A – level 90 %) and 37th (B – level 50 %) day after the start of the experiment. The period between these two points and further point B is a zone of complementary action of drugs. The complementarity zone is also observed with respect to thiamethoxam and nematode-fungal composition. Note the tendency to form omplementary pairs –according to the initial efficiency. This indicates the feasibility of simultaneous use of two or more drugs that complement each other in effectiveness. The use of population control means is carried out taking into account the thresholds of harmfulness, the models of which take into account the energy need for phytophagous nutrition, biomass of the plant root system and the effectiveness of protection technology in the previous period. For spring, summer and autumn, the threshold models are different. For forest ecosystems, it is advisable to increase the biological part of the protection system to 60–80 %, compared to the known ratio of chemical and biological methods (60:40), as the latter was established for acrocyanoses, taking into account not only the ecological component but also acceptable levels yield. Nursery threat from soil phytophagous is carried out for large areas according to the original protocol of the classification «penalty system» on the basis of scoring risk factors, and for local areas using a statistical method based on spatial distributions of the Swedberg criterion of plant attacks (percentage of death) and «pressure» of larvae on seedlings (reduction of growth to standard). Based on the results of the assessment, a management decision is made on the application of means of population regulation.
Keywords: ґрунтові фітофаги; хрущі; сосна звичайна; пороги шкідливості; хімічний та біологічний методи; регуляція чисельності; оцінка загрози молодим культурам; soil phytophages; beetles; Scots pine; harmfulness thresholds; chemical and biological methods